AB1072 The Assessment of Myopathy in Rheumatoid Arthritis – Vitamin D Status and Clinico-Biological and Electromyography Correlations. (9th June 2015) - Negru, M.M.; Berghea, F.; Balanescu, A.; Saulescu, I.; Groseanu, L.; Daia, S.; Bojinca, V.; Opris, D.; Predeteanu, D.; Ionescu, R.
Abstract : Background: Muscle damage is one of the least studied elements of the extra-skeletal manifestations of RA. Objectives: The evaluation of vitamin D levels in a group of patients with RA and clinical myopathy and establishing correlations with clinical and electromyographic muscle activity indices. Methods: We prospectively evaluated 50 patients with rheumatoid arthritis and myopathy and 21 healthy subjects, admitted in the Rheumatology Department of "St.Maria" Hospital between September 2013 and October 2014. Electromyographic exams were performed on all the patients in the active group, as well as on 11 subjects in the control group, who had consented to this procedure. I used the concentric needle method for recording MUP and quantitative analysis of multi-MUP. Vitamin D was assessed by measuring the serum level of 25(OH) vitamin D, using the Elisa methode. I focused on EMG correlation with the serum levels of vitamin D and the validated parameters of muscle testing (MRC force testing, chair rising test, TUG, TGT), titre of specific muscle enzymes or acute phase reactants, DAS28/HAQ. The analysis of the differences in distribution between the active group and the control group was made by Kruskal-Wallis test. Statistical correlations were tested by Pearson test. Results: The active group had an average age of 62.80 (11.51) years. The predominance of the female sex is noteworthy: the F/M ratio was 22:3 in the active group and 3.2:1 in the control group. The average serum levels of vitamin D in the active group were 28.94 (14.23) ng/ml; 28% of the subjects fit into insufficiency and 32% in the category of deficiency. In the control group, the average serum level of vitamin D was 31.96 (24.92), predominantly (52%) with deficiency. There was no statistically significant difference between the groups (p>0.05). In both groups, serum levels of vitamin D were significantly (p<0.05) higher in subjects whose blood samples had been collected in summer, as opposed to those whose blood had been sampled during winter. The percentage of subjects with values considered optimal was similar. The average duration of the disease in the active group was 12.68 (8.89) years and the average value of the disease activity score (DAS28) was 3.76 (1.44), 56% of patients with RA having a moderate or highly active form of the disease. EMG changes were better expressed in the active group with rheumatoid myopathy compared to the control group, especially for the studied parameters of the upper limb. 32 patients with RA had a short, myopathic duration of MUPs deltoid muscle and a myopathic duration in the first dorsal interosseous muscle was present at 22 patients. In the RA group, 27 patients had a complete, full interference pattern. The serum level of vitamin D was correlated with the clinical parameters for testing muscle weakness. Conclusions: The electromyographic changes more evident in the upper limb describe an inflammatory component of myopathy in RA, while predominant lower limb muscle damage has cortisone etiology. Lower limb muscle damage may be an indicator of myopathy in rheumatoid arthritis, related to the vitamin D level. References: Kimura J., Myopathies" in Neuromuscular junction, muscle disease and abnormal muscle activity", ed. 4: Oxford Univeristy Press, 2013: 841-889. Disclosure of Interest: None declared